Impacts of Distance Education System on Teacher Competency of Remote Schools in Lower Northern Thailand - Sakchai Petsuwan; Paitoon Pimdee; Phadungchai Pupat (My University, 2019)
Abstract This research aimed to study the impacts of Distance Education System on teacher Competency and compare teacher Competency before and after Distance Education System is applied. The sample was 28 teachers from four Remote Schools in lower Northern Thailand. Questionnaire was used as a data collection tool with reliability 0.99. Mean, Standard deviation and t-test for dependent samples were applied in data analysis process. The results showed that the Competency of teacher before Distance Education System had four competencies in moderate level including Working Achievement Motivation, Self- Development, Curriculum and Learning Management and Analysis & Synthesis & Classroom Research while other competencies were in high level. Distance Education System has positive impacts on teacher Competency as the every competency reaches high level after the system is applied with statistical significance at the level of 0.01.
Keywords: Statistical Analysis; Sample (material); Technology-Enhanced Education Studies